Thymus mastichina L. As a natural alternative for food preservation: study of bioactivities and phenolic profile - Pires Junior, Eleomar de O. (2022)
Market challenges are a strong promoter to innovation in the food preservatives segment, especially regarding consumer resistance to the use of artificial additives [1]. Plants belonging to the genus Thymus are traditionally used as spices in folk medicine and are characterized as promising sources of natural additives [2,3]. Thus, the present work aimed to identify and quantify the phenolic compounds and evaluate the bioactive properties of Thymus mastichina L., to validate its application as a natural preservative ingredient to be applied un the bakery and pastry industry. The chemical composition of Thymus mastichina L. aqueous extract was analyzed by chromatographic methods (HPLC-DAD-ESI/MS), followed by the identification of its individual compounds by comparison to literature data and commercial standards. To prove its bioactive properties, different in vitro tests were carried out to test its antioxidant properties (oxidative hemolysis inhibition (OxHLIA), reducing power, and free radical scavenging capacity (DPPH)), antimicrobial activity (evaluated using a panel of six bacteria and six filamentous fungi), anti-inflammatory action (in rat macrophage cells, RAW 264. 7), and cytotoxicity (in human tumor cell lines: MCF-7, breast carcinoma; NCI-H460, lung cancer; AGS, gastric carcinoma; and in non-tumor cells, PLP2 and Vero, by the sulforhodamine B method). Regarding the individual phenolic compounds, 12 distinct compounds were identified, derived from flavonoids and phenolic acids, in which kaempherol-O-hexuronoside stood out as the major compound. The antioxidant activity was the biological activity that stood out, with the extract presenting low EC50 values (0.048 ± 0.002 mg/mL, 0.035 ± 0.001 mg/mL, and 19.0 ± 0.6 μg/mL for DPPH, reducing power, and OxHLIA assays, respectively). In the cytotoxic assay, the extract showed higher efficiency for AGS cell line (59 ± 5 μg/mL), and for the antimicrobial activity, fungicidal (CMF) and bactericidal (CMB) potential was observed with a concentration range of 2 - 4 mg/mL. In general, based on the bioactive properties demonstrated by thyme extract, it can be considered as a natural ingredient with potential application in the food industry, attributing benefits to new food formulations, especially those developed in the bakery and pastry industry.